EDUKASI GERAK DASAR KIDS ATLETIK PADA GURU-GURU SEKOLAH DASAR KARANG ASIH, CIKARANG UTARA - Rizky Nurulfa; Iwan Setiawan; Mastri Juniarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Athletics is a mandatory sport in physical education in schools. Through athletic sports, children will have good basic movements. However, the application of subject matter for age levels must be given differently. Especially at the elementary school level. At the elementary school level, children have their event number which is contained in the kid's athletic competition number which is officially issued by the international organization World Athletics (WA). The understanding of this competition has not been known in more detail by sports teachers. For this reason, it is necessary to educate or discuss athletic sports for teachers, especially in areas not far from Jakarta, but they are still unable to simultaneously carry out this event. This activity was carried out at SMAN 1 Cikarang Utara, with a total of 37 teachers of Physical Education, Sports and Health (PJOK) who teach in elementary schools and basic education units. Before the education was carried out, the participants were given a post-test beforehand regarding their understanding of the athletic kid's event and basic athletic movements. As many as 40% already knew about competition numbers and simple rules. After being given material about athletic kids' numbers, athletic basic movements and athletic kids' competition rules, 82% were able to answer questions correctly. With these results, it can be concluded that this educational activity provides benefits to elementary school teachers in Cikarang Utara. Abstrak Atletik merupakan olahraga wajib pada pendidikan jasmani disekolah. Melalui olahraga alteltik anak-anak akan memiliki gerak adasar yang baik. Akan tetapi pada penerapan pemberian materi pelajaran untuk tingkat usia harus diberikan secara berbeda. Terutama pada tingkat sekolah dasar. Pada tingkat sekolah dasar anak-anak memliki nomor event sendiri yang tertuang dalam nomor perlombaan kids athletik yang remsi di keluarkan oleh organisasi internasional World Athletics (WA). Pemahaman tentang perlombaan ini belum banyak diketahui secara lebih detail oleh guru-guru olahraga. Untuk itu perlu dilakukan edukasi atau pemasalan olahraga atletik kepada guru-guru, terutama di wilayah yang tidak jauh dari jakarta, namun masih belum bisa serempak melaksanaan event ini. Kegiatan ini dilaksanaan di SMAN 1 Cikarang Utara, dengan jumlah peserta sebanyak 37 orang guru Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) yang mengajar di SD dan satuan pendidikan dasar. Sebelum dilaksanakan edukasi, para peserta diberikan post test terlebih dahulu mengenai pemahaman tentang event kids atletik dana gerak dasar atletik, Sebanyak 40% telah mengetahui tentang nomor-nomor perlombaan dan peraturan secara sederhana. Setelah di berikan materi tentang nomor-nomor kids atletik, gerak dasar atletik dan peraturan perlombaan kids atletik sebanyak 82% dapat menjawab pertanyaan dengan benar. Dengan hasil demikian dapat disimpulkan bahwa kegiatan edukasi ini memberikan manfaat kepada guru-guru SD di Cikarang Utara.